Corporate duties to the public / Barnali Choudhury, Martin Petrin. - Choudhury, Barnali, 1974-; Petrin, Martin, 1978- (Cambridge University Press, 2019)
In a world where the grocery store may be more powerful than the government and corporations are the governors rather than the governed, the notion of corporations being only private actors is slowly evaporating. Gone is the view that corporations can focus exclusively on maximizing shareholder wealth. Instead, the idea that corporations owe duties to the public is capturing the attention of not only citizens and legislators, but corporations themselves. This book explores the deepening connections between corporations and the public. It explores timely - and often controversial - public issues with which corporations must grapple including the corporate purpose, civil and criminal liability, taxation, human rights, the environment and corruption. Offering readers an encompassing, balanced, and systematic understanding of the most pertinent duties corporations should bear, how they work, whether they are justified, and how they should be designed in the future, this book clarifies corporations' roles vis-à-vis the public.